Contemporary genetic structure affects genetic stock identification of steelhead trout in the Snake River basin. Issue 19 (28th August 2020) - Powell, John H.; Campbell, Matthew R.
Abstract: Genetic stock identification is a widely applied tool for the mixed‐stock management of salmonid species throughout the North Pacific Rim. The effectiveness of genetic stock identification is dependent on the level of differentiation among stocks which is often high due to the life history of these species that involves high homing fidelity to their natal streams. However, the utility of this tool can be reduced when natural genetic structuring has been altered by hatchery translocation and/or supplementation. We examined the genetic population structure of ESA‐listed steelhead in the Snake River basin of the United States. We analyzed 9, 613 natural‐origin adult steelhead returning to Passive Integrated Transponder detection sites throughout the basin from 2010 through 2017. Individuals were genotyped at 180 single nucleotide polymorphic genetic markers and grouped into 20 populations based on their return location. While we expected to observe a common pattern of hierarchical genetic structuring due to isolation by distance, we observed low genetic differentiation between populations in the upper Salmon River basin compared to geographically distant populations in the lower Snake River basin. These results were consistent with lower genetic stock assignment probabilities observed for populations in this upper basin. We attribute these patterns of reduced genetic structure to the translocation of lower basin steelhead stocks and ongoing hatchery programs in the upper Salmon River basin. We discuss the implications of these findings on the utility of genetic stock identification in the basin and discuss opportunities for increasing assignment probabilities in the face of low genetic structure. Abstract : The genetic population structure of ESA‐listed steelhead in the Snake River basin of the United States was examined using 9, 613 natural‐origin adult steelhead returning to Passive Integrated Transponder detection sites from 2010 through 2017. We observed low genetic differentiation between populations in the upper Salmon River basin and geographically distant populations in the lower Snake River basin consistent with lower genetic stock assignment probabilities observed for populations in this upper basin. We attribute these patterns of reduced genetic structure to the translocation of lower basin steelhead stocks and ongoing hatchery programs in the upper Salmon River basin and discuss the implications of these findings on the implementation of genetic stock identification in the basin.